PEMANFAATAN MEDIA AUDIO VISUAL MELALUI STRATEGI PAILKEM UNTUK PEROLEHAN BELAJAR IPA SISWA KELAS IV - Ulfiah, Ulfiah; Syukri, M; Suib, Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine how far the utilization of audio-visual media through PAILKEM strategy in science for material parts of plant and its function of the students' acquisition at SDN 1 Sungai Kakap, runs well. This research uses Qualitative and Quantitative research method or mixed research. Qualitative research is used to describe instructional design and implementation of learning while quantitative research is used to measure how far the acquisition of learning outcomes obtained by grade IV. Data collection techniques used are observation, interview, and documentation. The results of the research are (1) science learning design using audio visual media in grade IV SDN 1 Sungai Kakap is done by teacher through preparing tools, curriculum, syllabus, text book, and audio visual learning media, designed in lesson plan; (2) Implementation of science learning by using audio visual media in general can be done well, it can help teacher and students in learning, and it can create active, innovative, environmentally, creative, effective and interesting learning; (3) Students learning acquisition by using audio visual media more increased that is 90% or 25 students who get the score over KKM and only 10% or 3 students who get the score same as KKM, with an average 90. It shows that the utilization of audio visual media through PAILKEM strategy for the learning achievement of science for grade IV students at Sekolah Dasar Negeri 1 Sungai Kakap, runs well, so the acquisition of student learning outcomes increases.Keywords: Utilization of audio visual media, PAILKEM strategy, learning acquisition.